Fostering Students’ Tolerance Character Through Structured Intercultural Dialogue at SMAN 9 Mataram - Febiyanti, Sari; Ningsih, Dewi Puspita; Rahmadi, Didin Septa; Hilmi, Muhamad Zoher (Primary Journal of Multidisciplinary Research, 2025)
This study aims to describe efforts to foster students’ tolerance character through structured intercultural dialogue at SMAN 9 Mataram, West Nusa Tenggara. The research background is based on the diverse religious, ethnic, and cultural backgrounds of students, which necessitates mutual respect and appreciation among peers. Employing a qualitative descriptive approach, the study involved teachers and students directly engaged in intercultural dialogue activities. Data were collected through observation, interviews, and documentation, and analyzed via data reduction, presentation, and conclusion drawing. Findings indicate that structured intercultural dialogue plays a significant role in nurturing students’ tolerance. Students are trained to respect differences, avoid discriminatory behavior, and develop understanding of diverse cultural and religious perspectives. Key supporting factors include a conducive school environment, active teacher involvement, and student and peer participation. Nonetheless, challenges remain, such as existing stereotypes, teasing, and exclusive behaviors among some students. Overall, this study confirms that structured intercultural dialogue can serve as an effective strategy to cultivate students’ tolerance character in multicultural school settings.